2016
DOI: 10.1007/s12576-016-0441-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology, immunophenotype, and gene expression characterization of senescent and cryopreserved human amniotic fluid stem cells

Abstract: We characterized human amniotic fluid stem cells (AFSC) in senescent cultures (6 weeks) versus cryopreserved cells using whole-cell patch-clamp, immunophenotyping, and differential gene expression profiling for senescence genes. We evidenced five ion current components (outward rectifier, A-type, inward rectifier, and big conductance Ca-dependent K currents, fast voltage-dependent Na currents). Senescent AFSC showed reduced expression of CD90, CD44, CD133, over 500-fold increase of interferon gamma and telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…However, the effective clinical translation of AFCs based approaches requires in vitro culture expansion to achieve a sufficient number of cells and strict characterization of the cultures, two factors that may severely hamper their clinical use [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effective clinical translation of AFCs based approaches requires in vitro culture expansion to achieve a sufficient number of cells and strict characterization of the cultures, two factors that may severely hamper their clinical use [5].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical phenotype of amniocytes in the present study, obtained via automated/manual whole-cell patch-clamp, is similar to that found in our previous studies on human amniocytes. 47 Using the same voltage protocols and combination of solutions, we found similar percentages of cryopreserved and senescent cells expressing certain ion current components, and similar current densities, with some exceptions. Thus, BK fluctuations were present in all cells included in the present study, and in only ~70% of both cryopreserved and senescent amniocytes in the 2016 study, and the percentage of senescent amniocytes featuring I Kir was higher in the present study.…”
Section: F I G U R E 4 Ion Currents Recorded In Amniocytes (A and B)mentioning
confidence: 61%
“…[39][40][41] Several studies explored different molecular changes associated with in vitro or in vivo senescence of MSC, including proteasome activation and autophagy, [42][43][44] effects of oxidative stress, 40,41 DDR and SAGA 45,46 in either control conditions or by induction of senescence via oxidative stress, doxorubicin, X-ray exposure or replicative exhaustion. 42 In a previous study 47 we demonstrated multiple differences between cryopreserved and senescent amniocytes including senescence-induced reduction in cell surface markers CD44, CD90, CD105, CD133 with preserved expression of CD29 and HLA-ABC, highly increased expression in senescent cells of in- Therefore, the aim of the present study is to further explore activation of specific signalling pathways associated with SASP and SAGA in our in vitro senescence model, and to correlate them with changes in ion currents assessed via automated or manual patch-clamp.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations